Canvi lexicosemàntic: salpuscar 'esquitar' i variants, un petit enigma. - MARTINES, JOSEP (Scripta)
This article shows what must have been the origin of the Catalan verb salpuscar and its variant salbuscar, synonym of the current verb esquitar o esquitxar ('to splash'). It highlights the possibilities offered by digital textual corpora and the need to bear in mind the contrastive study of languages (especially when it comes to Occitan) and the cultural history when diachronic semantics and lexicology of Catalan are done. Likewise, basic notions of cognitive semantics are applied in the study of linguistic change.